Multiomics Analyses of Two Sorghum Cultivars Reveal the Molecular Mechanism of Salt Tolerance - Ren, Genzeng; Yang, Puyuan; Cui, Jianghui; Gao, Yukun; Yin, Congpei; Bai, Yuzhe; Zhao, Dongting; Chang, Jinhua (Frontiers in Plant Science, 2022)
Sorghum [Sorghum bicolor (L.) Moench] is one of the most important cereal crops and contains many health-promoting substances. Sorghum has high tolerance to abiotic stress and contains a variety of flavonoids compounds. Flavonoids are produced by the phenylpropanoid pathway and performed a wide range of functions in plants resistance to biotic and abiotic stress. A multiomics analysis of two sorghum cultivars (HN and GZ) under different salt treatments time (0, 24, 48, and 72) was performed. A total of 45 genes, 58 secondary metabolites, and 246 proteins were recognized with significant differential abundances in different comparison models. The common differentially expressed genes (DEGs) were allocated to the “flavonoid biosynthesis” and “phenylpropanoid biosynthesis” pathways. The most enriched pathways of the common differentially accumulating metabolites (DAMs) were “flavonoid biosynthesis,” followed by “phenylpropanoid biosynthesis” and “arginine and proline metabolism.” The common differentially expressed proteins (DEPs) were mainly distributed in “phenylpropanoid biosynthesis,” “biosynthesis of cofactors,” and “RNA transport.” Furthermore, considerable differences were observed in the accumulation of low molecular weight nonenzymatic antioxidants and the activity of antioxidant enzymes. Collectively, the results of our study support the idea that flavonoid biological pathways may play an important physiological role in the ability of sorghum to withstand salt stress.